Pre-race deep-breathing improves 50 & 100-yard swim performance in female NCAA swimmers. Manuscript and coaching applications - Gray, T. O.; Pritchett, R.; Pritchett, K.; Burnham, T. (Journal of Swimming Research, 2018)
The purpose of this study was to examine the effects of a 30sec or 2min deep-breathing exercise on a 50-yard and 100-yard freestyle performance. Methods: Seven competitive female NCAA (Division I and Division III) swimmers performed a 50-yard and 100-yard freestyle sprint either in normal conditions (DBNO) after deep-breathing of 30sec (DB30) or 2min (DB2) of deep-breathing. Results: Average velocity for the 50-yard freestyle was not significantly faster after the DB30 (DBNO 1.76 ± 0.12 y/s vs. DB30 1.77 ± 0.10 y/s P = 0.37). Average velocity for the 100-yard freestyle was also not significantly faster for the DB30 (DBNO 1.63 ± 0.11 y/s vs. DB30 1.63 ± 0.13 y/s P = 0.62). However, faster swim times were observed in both the 50-yard freestyle (50 free: DBNO 28.45 ± 1.90sec vs. DB30 28.18 ± 1.59sec, P > 0.23).and 100 freestyle (100 free: DBNO 61.73 ± 4.33sec vs. DB30 61.54 ± 5.11sec P = 0.79) after DB30. The DB2 resulted in slower swim times for both 50 and 100-yard swims when compared to DBNO (DBNO 28.45 ± 1.90sec vs. DB2 28.85 ± 2.21sec P = 0.29; DBNO 61.73 ± 4.33sec vs. DB2 62.15 ± 5.52sec P = 0.58, respectively). Conclusions: A pre-race, voluntary 30sec deep-breathing procedure resulted in slight improvement in time for the 50-yard and 100-yard freestyle race, which could potentially translate to a competitive advantage.